SOSIALISASI PENCEGAHAN PENYALAHGUNAAN NARKOTIKA DI DESA GUNUNG KELAMBU KABUPATEN TAPANULI TENGAH - Sipahutar, Hadijah; Hadia Lubis, Rifka; Nur Simamora, Fauziah (COVIT (Community Service of Tambusai), 2022)
Circulation and abuse of drugs is one of the national problems that is considered serious by the government, because it can cause damage to the nation’s morale. Therefore, the government pays great attention to the handling of drug abuse. In our country, the problem of widespread drug abuse is increasing. The domino effect resulting from drug abuse is also increasingly diverse, and efforts to overcome drug abuse are steps that are not easy to implement. Abusers are people who use Narcotics without rights or against the law. When a person abuses Narcotics continuously, then that person will be in a state of dependence on Narcotics, both physically and psychologically. Narcotics dependence is a condition characterized by an urge to use Narcotics continuously with increasing doses to produce the same effect and when its use is reduced and/or stopped suddenly, it causes characteristic physical and psychological symptoms. Society has an important role in preventing and overcoming drug abuse. For this reason, community leaders can carry out the following things: Understand the problem of drug abuse, prevention and control. Observe the situation and environmental conditions. Galang community potentials that can help implement the prevention, especially parents, teenagers, schools, social organizations in the community in Indonesia. around the environment. Direct, encourage and control the movement of the community. Keywords: Narcotics, Prevention.